Linguistic Dominance and Translanguaging: Language Issues in Generations: The Legacy - Kealeboga Aiseng (Frontiers in Communication, 2022)
The use of language(s) in media is very important as it can determine inclusion or exclusion. As such, the use of language in the media is contentious. This paper traces two language issues in one of the SABC's longest-running soap operas, Generations: The Legacy, language ideology and a tool against that language ideology. The former refers to a linguistic dominance of isiZulu and the latter refers to translanguaging. With the use of transcription data analysis and audio-visual analysis, the current study has concluded that there are issues of linguistic dominance and translanguaging in Generations: The Legacy. These language issues are perpetuated through the narrative and characters of the story. The appropriate theoretical framework for this paper is the use of language in popular culture, with the view that the use of languages in popular culture can exclude and include, can empower, and disempower. Focusing on the dialogues of the soap using selected episodes as case studies for analysis, the study has also concluded that creative decisions made in the soap are ideological. These findings raise questions about the use of media to perpetuate certain language ideologies and raise questions about whose interests are served by these language ideologies and how to fight these language ideologies.